Determination of mazindol in human oral fluid by high performance liquid chromatography–electrospray ionization mass spectrometry. (23rd January 2014) - de Oliveira, Marcella Herbstrith; Carlos, Graciela; Bergold, Ana Maria; Pechansky, Flavio; Limberger, Renata Pereira; Fröehlich, Pedro Eduardo
ABSTRACT Brazil is one of the countries most affected by abuse of stimulant medications by professional drivers, especially fenproporex, amfepramone and mazindol. Even though their sale is banned, they can be found in illegal markets, such as those located on the country's borders. The use of oral fluid to monitor drug levels has many advantages over plasma and urine because it is noninvasive, easier to collect and more difficult to adulterate. The aim of this study was to develop and validate a sensitive and specific method to quantify mazindol in human oral fluid by liquid chromatography–mass spectrometry (LC‐MS). The LC system consisted of an LC‐MS system operated in selected ion monitoring mode. The mobile phase was composed of water at pH 4.0, acetonitrile and methanol (60:15:25 v/v/v) at a flow rate of 1.0 mL/min and propranolol was used as internal standard. Total running time was 10 min. The lower limit of quantification was 0.2 ng/mL and the method exhibited good linearity within the 0.2–20 ng/mL range (r = 0.9987). A rapid, specific, sensitive, linear, precise and accurate method was developed for determination of mazindol in human oral fluid according to European Medicines Agency guidelines, and is suitable for monitoring mazindol levels in oral fluid of professional drivers. Copyright © 2014 John Wiley & Sons, Ltd.